Design and Realization of System Structure Based on Blackboard System - R.Z. Chu; S.J. Sun; L. Yang (Institute of Advanced Engineering and Science, 2013)
This paper discusses design environment of software system structure of blackboard style, which ascertain out the job pattern the blackboard decision-making model. At last, let’s list regarding a mobile robotics architecture primary need and realize the characteristic to the blackboard system pattern in the quality demand to carry on the analysis, taking floor intelligence robot software system as example. Finally the quality and ability of the four patter in architecture classification has been compared. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3082